Identification of a critical role for ZIKV capsid α3 in virus assembly and its genetic interaction with M protein. - Anastazia Jablunovsky; Anoop Narayanan; Joyce Jose (PLoS Neglected Tropical Diseases, 2024)
Flaviviruses such as Zika and dengue viruses are persistent health concerns in endemic regions worldwide. Efforts to combat the spread of flaviviruses have been challenging, as no antivirals or optimal vaccines are available. Prevention and treatment of flavivirus-induced diseases require a comprehensive understanding of their life cycle. However, several aspects of flavivirus biogenesis, including genome packaging and virion assembly, are not well characterized. In this study, we focused on flavivirus capsid protein (C) using Zika virus (ZIKV) as a model to investigate the role of the externally oriented α3 helix (C α3) without a known or predicted function. Alanine scanning mutagenesis of surface-exposed amino acids on C α3 revealed a critical CN67 residue essential for ZIKV virion production. The CN67A mutation did not affect dimerization or RNA binding of purified C protein in vitro. The virus assembly is severely affected in cells transfected with an infectious cDNA clone of ZIKV with CN67A mutation, resulting in a highly attenuated phenotype. We isolated a revertant virus with a partially restored phenotype by continuous passage of the CN67A mutant virus in Vero E6 cells. Sequence analysis of the revertant revealed a second site mutation in the viral membrane (M) protein MF37L, indicating a genetic interaction between the C and M proteins of ZIKV. Introducing the MF37L mutation on the mutant ZIKV CN67A generated a double-mutant virus phenotypically consistent with the isolated genetic revertant. Similar results were obtained with analogous mutations on C and M proteins of dengue virus, suggesting the critical nature of C α3 and possible C and M residues contributing to virus assembly in other Aedes-transmitted flaviviruses. This study provides the first experimental evidence of a genetic interaction between the C protein and the viral envelope protein M, providing a mechanistic understanding of the molecular interactions involved in the assembly and budding of Aedes-transmitted flaviviruses.